Tools for causality assessment in drug-induced liver disease. Issue 3 (May 2019) - Tillmann, Hans L.; Suzuki, Ayako; Barnhart, Huiman X.; Serrano, Jose; Rockey, Don C.
Abstract : Purpose of review: There are three liver-specific causality assessment tools currently available to guide clinical diagnosis of Drug-Induced Liver Injury (DILI): Roussel-Uclaf Causality Assessment Method (RUCAM), Digestive-Disease-Week Japan 2004 scale (DDW-J), and Clinical Diagnostic Scale (CDS). The purpose of this review is to assess these tools and discuss how to improve the causality assessment process as a whole. Recent findings: Existing DILI-specific causality assessment tools are surprisingly similar and exhibit only minor differences in point allocation. But difference in threshold for likelihood of being DILI. We reviewed the literature on currently used causality assessment tools, identified areas for future improvement, and herein propose approaches for refinement. Opportunities to improve current models, as well as the assessment process, in general, include in particular provision of more precise clinical detail and to perhaps add new components to scoring systems. For example, the incorporation of drug-specific clinical signature patterns, accounting for a drug's inherent hepatotoxicity potential, and/or incorporation of other drug properties to scoring systems may allow enhancement. Further, more systemic exclusion of competing diagnoses is needed. Finally, causality assessment processes will likely benefit from a data-driven and computer-assisted approach. Summary: Current tools used for DILI adjudication are imperfect. Avenues to improve these tools are described.